Analisis Kontribusi Pajak dan Retribusi Terhadap Pendapatan Asli Daerah - Yuliza Azzahra Syahadat; Dirga Ramadhan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Regional taxes and regional levies are the two components of the most dominant source of income for Regional Original Revenue (PAD) which are useful for financing the administration of regional governments to carry out broad regional autonomy in a good, real and responsible manner. This study aims to determine the contribution of local taxes and local levies to (PAD) Kendari city. The data used is the report on the realization of the budget for the 2018-2020 fiscal year. Data analysis using Contribution percentage analysis, Contribution Level Analysis and Growth. The results of this study show that local revenue is very dependent on local tax revenues and regional levies with a large percentage of local taxes on PAD in 2018 of 58.61%, the percentage of regional retribution on PAD of 11.94%. In 2019, the percentage of local taxes to PAD was 55.55%, the percentage of regional levies to PAD was 11.12%. In 2020 the percentage of local taxes to PAD is 52.68%, the percentage of regional levies to PAD is 8.01%. From this explanation, it is stated that the contribution of taxes to Regional Original Income (PAD) is greater than the regional levies.